« Les pieds toujours dans la classe » - Daniela Vitagliano (Contextes)
In this contribution, our aim is to interpret the category of “transfuge de classe” through the lens of what we consider its archetype: “the victim”. This approach will allow us to assess the operability of this category and explore its potential as a literary paradigm capable of generating reflections on social conflicts and the collective impact of individual experiences. Our analysis focuses on the case of Italy, which, though seemingly close to France, has a rather different social and economic structure, particularly regarding the perception of work and education. By examining the works of Alberto Prunetti, Vitaliano Trevisan, Claudia Durastanti, Johnatan Bazzi, and Elena Ferrante, we will investigate the elements that might allow us to interpret these authors and their works as “transfuge de classe narratives”.